Electronic structure changes during the surface-assisted formation of a graphene nanoribbon - Bronner, Christopher; Utecht, Manuel; Haase, Anton; Saalfrank, Peter; Klamroth, Tillmann; Tegeder, Petra (The journal of chemical physics, 2014)
High conductivity and a tunability of the band gap make quasi-one-dimensional graphene nanoribbons (GNRs) highly interesting materials for the use in field effect transistors. Especially bottom-up fabricated GNRs possess well-defined edges which is important for the electronic structure and accordingly the band gap. In this study we investigate the formation of a sub-nanometer wide armchair GNR generated on a Au(111) surface. The on-surface synthesis is thermally activated and involves an intermediate non-aromatic polymer in which the molecular precursor forms polyanthrylene chains. Employing angle-resolved two-photon photoemission in combination with density functional theory calculations we find that the polymer exhibits two dispersing states which we attribute to the valence and the conduction band, respectively. While the band gap of the non-aromatic polymer obtained in this way is relatively large, namely 5.25 ± 0.06 eV, the gap of the corresponding aromatic GNR is strongly reduced which we attribute to the different degree of electron delocalization in the two systems.